Theoretical-methodological Notes for the Study of Brazilian Political Thought: Contextualism, Political Development, Peripheral Condition - Lynch, Christian Edward Cyril; Cassimiro, Paulo Henrique Paschoeto (Revista do Instituto Histórico e Geográfico Brasileiro, 2023)
The article explores some theoretical- methodological problems for the study of Brazilian political thought, focusing on three main axes. Firstly, understanding the context problems for the interpretation of the transformation, circulation and reception of ideas. Secondly, the formulation of a political development model as an organizing axis for a comparative interpretation of political thought, in relation to the constitutive problems of political modernity (the formation of the State, constitutionalism, the construction of representative government, the expansion of representation, etc.). Thirdly, the development of a notion of “peripheral condition” that allows us to understand the comparative specificities of the displacement of ideas in relation to their canter of origin. In the end, we intend to offer some contribution to a type of practice of political thought that lies between political theory and the history of ideas.